The early pregnancy in mares - What do we still not know? - Marta Siemieniuch-Tartanus (Veterinary and Animal Science)
Equine conceptus development is a critical study area due to its significant implications for the equine breeding industry. Following a high fertilization success rate of 71–96 % (Ball, 1988), it is concerning that 30–40 % of developing embryos may not survive beyond the crucial initial two weeks of gestation, coinciding with the onset of gastrulation (Ball, 1988).The pregnancy in mares lasts 330–345 days. The underlying molecular mechanisms of the embryonic period are not fully explained in mares. During early pregnancy in mares, the following takes place: the descent of the blastocyst from the oviduct to the uterus around 5–6 days post-fertilization; migration of the spherical conceptus, surrounded by a glycoprotein capsule in the uterine lumen; fixation of the vesicle near the base of the uterine horn around 16–17 days post-fertilization; implantation; development of endometrial cups that produce chorionic gonadotropin, as well as an additional corpus luteum that produces progesterone. In mares, there is no clear determination of what constitutes the early signal of pregnancy recognition. The results of previous research indicate that mechanical stimuli, i.e. the movement of the conceptus in the uterine lumen, trigger a cascade of molecular events in the endometrium responsible for the luteostasis and the maintenance of early pregnancy in mares.This study aims to provide a synthetic summary of the knowledge we have gained so far about early pregnancy and to attempt to answer the question of what molecular mechanisms underlie maternal recognition of pregnancy in mares.